Butterfly spices diversity and abundance in university of Ibadan botanical garden, Nigeria (2015)
Understanding the significance of butterflies in an ecosystem as an environmental healthy indicator and pollination of flowering plants is crucial to achieving sustainability and conservation of floral diversity. The aim of the study was to investigate the butterfly species diversity and abundance and compare the relationship between physical factor and butterfly species. Line transect were used to survey three habitats around botanical garden with scooped-net between June and July, 2010. Diversity varied from habitat to habitat. A checklist was made comprising a total of 57 butterfly species that were surveyed belonging to 9 families. There was a relationship between temperature and butterfly species diversity and abundance. There was no correlation between physical factors (relative humidity and temperature) and the total number of species and families. Moreover, butterfly numbers were not related to relative humidity in any species and family. However, temperature was significantly correlated with species. Therefore, understanding of the factors that affect butterfly species diversity and abundance in University of Ibadan Botanical Garden is important for conservation.